Nocturnal Sleep Problems Mediate the Impact on Quality of Life of Early Morning Off in Parkinson's Disease - Zhang, Yu; Zhang, Zi en; Shi, De; Zhao, Yi; Huang, Lihong; Zhao, Yanxin; Wang, Hui; Zhao, Jing; Wang, Feng; Zhao, Chaorong; Gao, Shan; Wei, Wenshi; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Early morning off (EMO) refers to off-states in the morning in people diagnosed with Parkinson's disease (PwPD). Our study determined the clinical manifestations of EMO and the association with nocturnal sleep problems and quality of life in Chinese PwPD. Methods: In this multicenter, observational, cross-sectional study, data concerning the clinical manifestations of EMO were collected from PwPD in Shanghai by questionnaire. Stepwise logistic regression was performed to analyze potential risk factors, as well as whether EMO was an independent risk factor for functional dependency in daily life. Mediation analyses were conducted to evaluate whether nocturnal sleep problems might mediate the association between EMO and the quality of life. Results: Among the 454 subjects evaluated, EMO occurred in 39.43% of PwPD across all disease stages. The prevalence of EMO increased as the Hoehn and Yahr stage increased, and was observed in 35.60% of Stage 1-2.5 patients and 48.85% of Stage 3-5 patients. EMO was associated with non-motor symptoms (NMSs). The predominant NMSs associated with EMO were nocturnal sleep problems (98.90%), mood/cognition impairment (93.90%), decreased attention/memory (91.60%), gastrointestinal symptoms (91.60%), and urinary urgency (90.50%). The quality of life of PwPD with EMO was significantly reduced (p＜ 0.001). Moreover, nocturnal sleep problems might partially mediated this relationship (indirect effect: β = 13.458, 95% boot CI: 6.436, 22.042). Conclusion: PwPD have EMO throughout all stages of the disease. Patients with EMO have severe motor and non-motor symptoms. EMO is associated with decreases the quality of life in PwPD and this relationship is partially mediated by nocturnal sleep problems. In light of these findings, it is suggested that recognition and appropriate treatment of EMO and nocturnal sleep problems could improve the management of PwPD.